The Influence of Price (VAT) and Brand Image on Purchase Decisions of Scarlett Skincare Products in TikTok Shop through Consumer Trust as a Mediating Variable among Generation Z in Indonesia - Dela Aprilia; Zaenul Muttaqien (LP2M IAIN Palopo, 2025)
This study aims to examine the effect of Price (VAT) and Brand Image on Purchase Decisions of Scarlett skincare products through TikTok Shop, with Consumer Trust serving as both a mediating and moderating variable among Generation Z in Indonesia. A quantitative approach was employed, targeting Generation Z consumers who have purchased Scarlett products via TikTok Shop. The sample was determined using purposive sampling, with the criteria of respondents aged 13–28 years. Based on the Rao Purba formula, the minimum required sample size was 96.4 respondents, rounded up to 100, which is considered appropriate according to Roscoe’s rule of thumb suggesting an ideal range of 30 to 500 respondents. Data were collected using questionnaires with a five-point Likert scale and analyzed with SmartPLS software. The findings reveal that Price (VAT), Brand Image, and Consumer Trust have a positive and significant effect on Purchase Decisions, both directly and indirectly. More specifically, Consumer Trust plays a mediating role in strengthening the influence of Price (VAT) and Brand Image on Purchase Decisions. Thus, Consumer Trust emerges as a key factor that bridges and reinforces the interrelationships among the variables, resulting in a more consistent and significant impact on Purchase Decisions